Village Fund Allocation Programme in The Development of Seriwe Village Lombok Timur - Mohzana Mohzana; Muh. Fahrurrozi (Cita Konsultindo Research Center, 2023)
The allocation of village funds is a source of village income that plays a very important role in the implementation of government, development, community development and community empowerment. The purpose of this research is to analyse the implementation of the Village Fund Allocation program and its role in improving community welfare in Seriwe Village, Jerowaru District, East Lombok Regency. The type of research used is qualitative research using descriptive analysis. Based on field research and data analysis that has been carried out by researchers, the results obtained in general are the implementation of the Village Fund Allocation in Seriwe Village is running effectively and efficiently as seen from the results of the programme that are in accordance with the objectives of improving community welfare. The Village Fund Allocation programme can solve existing problems. The responsiveness of the community is quite good with the existence of village development plan deliberation activities and the accuracy of the Village Fund Allocation programme in Seriwe Village is considered beneficial for the community and community institutions.